Pengaruh Leverage dan Pertumbuhan Penjualan terhadap Profitabilitas pada Perusahaan Subsektor Tekstil dan Garmen - Widhi, Niluh Nugrahaning; Suarmanayasa, I Nengah (Universitas Pendidikan Ganesha, 2021)
Companies with good performance are able to achieve the goals the company wants to achieve, namely maximizing company value. This goal can be achieved by increasing the profitability of a company. The purpose of this study was to determine the effect of leverage, sales growth simultaneously and partially on profitability. This research was conducted at the textile and garment subsector companies in the Indonesia Stock Exchange with a sample of 17 companies obtained through the purposive sampling method. The results of the study with multiple linear regression analysis found that:Â (1) Leverage and sales growth have a significant effect on profitability. (2) Leverage has a negative and significant effect on profitability. (3) Sales growth has a positive and significant effect on profitability